Presentation of the research program «INTERLOR - Lotharingien und das Papsttum. Interaktions-, Integrations- und Transformationsprozesse im Spannungsfeld zwischen zentraler Steuerung und regionaler Eigendynamik (11. - Anfang 13. Jahrhundert)» (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The text outlines the research project «Interlor. Lotharingia and the Papacy. Processes of Interaction, Integration, and Transformation between Central Regulation and Regional Dynamics (11th-13th century)» funded by the Deutsche Forschungsgemeinschaft (DFG) and the Fonds National de la Recherche (FNR) of Luxembourg. In January 2021, it started as a joint enterprise of the universities of Luxembourg and Aachen aiming at an extensive enquiry of the relations between the papacy and Lotharingia (i. e. the region between Utrecht and southern Lorraine) in the High Middle Ages. The project focuses on forms of reciprocal communication and their impact on regional development in different aspects. For example, the use and form of script, cathedral cities, religious orders, or structures of secular government are taken into consideration. This will sharpen the profile of Lotharingia as a zone of transfer and contact between Germany and France. In contrast to traditional tracks of research which concentrated almost on the interaction with the peripheries of Europe, now a region of its very centre is addressed. Consequently, it may open new prospects on the way the papacy tried to establish its absolute claim to leadership in the Latin church.
Keywords: Papacy; Lotharingia; Gregorian reform; Cistercians; Premonstratensians; Papal letters